The Struggle Of Achyat Chalimy Through Laskar Hizbullah In The Independence Revolution 1945-1950 - Winarno, Novyantika Eka Putri; Marjono, Marjono; Sumardi, Sumardi; Umamah, Nurul; Surya, Riza Afita (History Education, University of Jember, 2022)
Achyat Chalimy is a student of KH. Hasyim Asy'ari who founded Laskar Hizbullah Mojokerto in 1945 to defend Indonesia's independence. The formation of Laskar Hizbullah was recognized by Japan on December 15, 1944. Laskar Heizbullah was a semi-military force consisting of Muslim youths and students who fought to defend Indonesia's independence against allied forces. The purpose of this study was to analyze the role of Achyat Chalimy and Laskar Hizbullah in the Revolution of Independence in 1945-1950. This research uses historical research methods and social psychology approaches. The results of this study indicate that Achyat Chalimy and Laskar Hezbollah during the Independence Revolution played a role in the battle in Surabaya in 1945, the guerrilla battle in Mojokerto in 1945-1947, and the battle in Kutorejo in 1948-1949. The end of Achyat Chalimy's role with Laskar Hizbullah in 1950 was marked by the transfer of sovereignty from the Netherlands to Indonesia. Keywords: Achyat Chalimy, Laskar Hizbullah, Independence Revolution